ANALISIS PENGARUH KUALITAS PELAYANAN DAN BRAND IMAGE TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA PELANGGAN JASA EKSPEDISI JNE EXPRESS DI KOTA SEMARANG) - Zalzabilla, Annisa; Yuliati, Yuliati (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
This study aims to explain the effect of Service Quality and Brand Image on Customer Loyalty through Customer Satisfaction as an intervening variable on JNE Express expedition service customers in Semarang City and to determine the effect of Service Quality, Brand Image, Customer Satisfaction on Customer Loyalty. The research method used is Path Analysis. The sample in this study amounted to 105 people using a non-probability sampling technique with a purposive sampling approach, namely the study selected samples intentionally and subjectively. Based on the results of the analysis, it shows that: Service Quality has a positive and significant effect on Customer Satisfaction as evidenced by the t-value of 1.877> t-table 1.659 and a significance level of 0.000 <0.05. Brand Image has a positive and significant effect on Customer Satisfaction as evidenced by the t-value of 2.582> t-table 1.659 and a significance level of 0.000 <0.05. Service Quality has a positive and significant effect on Customer Loyalty as evidenced by the t-value of 5.506> t-table 1.659 and a significance level of 0.000 <0.05. Brand Image does not have an effect on Customer Loyalty as evidenced by the t-value of 1.172> t-table 1.659 and a significance level of 0.244> 0.05. Customer Satisfaction does not have an effect on Customer Loyalty as evidenced by the t-value of 0.295 > t-table 1.659 and a significant level of 0.069 > 0.05. Service Quality has a positive and significant effect on Customer Loyalty through Customer Satisfaction as evidenced by the direct effect value of 0.447 < indirect effect of 0.564. Brand Image has a positive and significant effect on Customer Loyalty through Customer Satisfaction as evidenced by the direct effect value of 0.285 < indirect effect of 0.402.Keywords: Service Quality, Brand Image, Customer Satisfaction and Customer Loyalty